African music and its use in the school: an investigation - Petersen, Alvin Benito (College of Music, 2024)
The purpose of this dissertation is to investigate the educational possibilities of African music in all schools. To the best of the author's knowledge, African music is almost completely ignored in most non-African schools in South Africa, and where it is taught, the essential elements which make the music "African" are almost completely ignored. It seems deplorable that such a rich musical resource has hardly been tapped in the non-African school. This state of affairs comes about because of negative attitudes towards things African in general and towards the African in particular. In his research in the Western Cape, the author has found that Africans no longer play traditional musical instruments such as the bow and that there is an increasing tendency to move away from traditional musical instruments in favour of Western ones. It is hoped therefore that this dissertation will lead to an appreciation of African music at all schools and that it will somehow contribute towards the revival of bow-playing in urban African communities, because a large part of this dissertation is devoted towards bow-playing and its possible uses in the school. This dissertation is in two parts: the first is a broad systematic introduction to African music, with special reference to African music in South Africa. In this section musical aspects such as form, harmony and rhythm are discussed separately. The influence of speech on song and categories of Nguni song are also included in this section. There are also detailed descriptions of some of the instrumental types in Africa and their uses in society. It should be stressed that the. terminology used in both parts, for example, 'cross-rhythm', is not necessarily the terminology used by the Africans, but is used here to facilitate understanding by all.